Novel congenital disorder of O-linked glycosylation caused by GALNT2 loss of function. - Zilmer, Monica; Edmondson, Andrew C; Khetarpal, Sumeet A; Alesi, Viola; Zaki, MAH S; Rostasy, Kevin; Madsen, Camilla G; Lepri, Francesca R; Sinibaldi, Lorenzo; Cusmai, Raffaella; Novelli, Antonio; Issa, Mahmoud Y; et al. (Brain, 2020)
Congenital disorders of glycosylation are a growing group of rare genetic disorders caused by deficient protein and lipid glycosylation. Here, we report the clinical, biochemical, and molecular features of seven patients from four families with GALNT2-congenital disorder of glycosylation (GALNT2-CDG), an O-linked glycosylation disorder. GALNT2 encodes the Golgi-localized polypeptide N-acetyl-d-galactosamine-transferase 2 isoenzyme. GALNT2 is widely expressed in most cell types and directs initiation of mucin-type protein O-glycosylation. All patients showed loss of O-glycosylation of apolipoprotein C-III, a non-redundant substrate for GALNT2. Patients with GALNT2-CDG generally exhibit a syndrome characterized by global developmental delay, intellectual disability with language deficit, autistic features, behavioural abnormalities, epilepsy, chronic insomnia, white matter changes on brain MRI, dysmorphic features, decreased stature, and decreased high density lipoprotein cholesterol levels. Rodent (mouse and rat) models of GALNT2-CDG recapitulated much of the human phenotype, including poor growth and neurodevelopmental abnormalities. In behavioural studies, GALNT2-CDG mice demonstrated cerebellar motor deficits, decreased sociability, and impaired sensory integration and processing. The multisystem nature of phenotypes in patients and rodent models of GALNT2-CDG suggest that there are multiple non-redundant protein substrates of GALNT2 in various tissues, including brain, which are critical to normal growth and development.
Keywords: Adolescent; Animals; Apolipoprotein C-III; Child; Child, Preschool; Developmental Disabilities; Female; Glycosylation; Humans; Loss of Function Mutation; Male; Mice; N-Acetylgalactosaminyltransferases; Pedigree; Rats; Young Adult